'...to read people differently'.: The purpose of English Literature in English secondary schools. (3rd July 2022) - Perry, John
ABSTRACT: This article takes Margaret Meek Spencer's 1988 pamphlet "How Texts Teach What Readers Learn" to frame a discussion about the purpose of English Literature in English secondary schools. The primary data informing this article is taken from original interviews with ten Heads of English departments in English secondary schools. Henri Lefebvre's framework of conceived, perceived and lived spaces is used to analyse the data to understand how the Heads of Department conceptualise the place and purpose of English Literature in their schools. The views of the Heads of English are then discussed in light of Meek Spencer's work, highlighting how the current curriculum for English Literature produces a subject which is at odds with her ideas and contemporary views of the English curriculum and its purpose. The article concludes with some suggestions about how the teaching of English Literature in schools can be developed so that it is more in line with Meek Spencer's ideas, is more socially just and more ambitious.